Ankle and Distal Tibia Megaprostheses in Orthopedic Oncology: A Report of Two Cases and Review of the Literature - Edoardo Ipponi; Martina Cordoni; Elena Bechini; Fabrizia Gentili; Fabio Cosseddu; Antonio D'Arienzo; Lorenzo Andreani (Acta Medica Lituanica)
Background: The distal tibia is one of the rarest sites for the onset of malignant and locally aggressive bone tumors. When diagnosed, these lesions should undergo surgical resection with wide margins to eradicate the disease. In the era of limb-sparing surgery, several reconstructive approaches have been proposed and described in modern literature for reconstructing the distal tibia and the ankle. The 3D-printed custom-made prostheses represent an innovative and promising reconstructive option. Several authors highlighted that despite being expensive and prone to some complications such as talar collapse or loosening and soft tissue necrosis, the megaprostheses of the distal tibia could lead to good functional outcomes, also allowing a better range of motion compared to the most common arthrodesis. Materials and methods: We report two cases who suffered from malignant bone tumors localized in the distal tibia and treated with wide resections and the implant of 3D printed custom-made megaprostheses to replace the distal tibia and the ankle. Results: Both patients had excellent functional results (MSTS 30/30) one year after surgery. No local recurrence occurred during the patients’ latest follow-up. Conclusions: Our results support the effectiveness of custom-made implants in replacing the distal tibia and the ankle in orthopedic oncology.